Exploration of the Relationship between Organizational Culture and Its Performance in the Bangladeshi Microfinance Sector with Organizational Innovation as a Mediating Factor - Akhter, Parul; Chaity, Naznin Sultana (European Scientific Journal, ESJ, 2024)
This study aims to explore the relationship between organizational culture and organizational performance, whereas organizational innovation is focused on as a mediating variable in the microfinance organization in Bangladesh. The current study looks at organizational culture, covering mission, employee involvement, and adaptability. Organizational performance is defined by four variables: productivity, effectiveness, efficiency, and quality, while organizational innovation is determined by four variables: innovation strategy, intellectual capital, new process development, and new product development. The study used a self-administered questionnaire using a five-point Likert scale. The data were collected from 300 middle and senior managers and considered Bangladesh’s top fifty microfinance organizations. The hypotheses and connections between the constructs were empirically tested using structural equation modeling (SEM) along with the partial least squares (PLS) approach. The findings indicate that organizational culture positively affects organizational innovation and firm performance. Organizational innovation has a strong positive impact on organizational performance. On the other hand, organizational innovation mediates the indirect relationship between organizational culture and performance. The study’s findings indicate that executives, entrepreneurs, and policy developers should focus on business culture and organizational innovation in addition to increasing efficiency and maintaining a competitive advantage.